A Comparative Study of Different Acids used for Sandstone Acid Stimulation: A Literature Review - Van Hong, L.; Ben Mahmud, Hisham (IOP Publishing, 2017)
© Published under licence by IOP Publishing Ltd. Matrix acidizing is an effective well stimulation technique, in which acids are injected at a pressure below the formation fracture pressure. The application of sandstone matrix acidizing has been widely used in the oil and gas industry for many decades. The application of mud acid, which is a combination of Hydrofluoric acid and Hydrochloric acid (HF:HCl) in well stimulation, has gained its popularity in improving the porosity and permeability of reservoir formation. In fact, this is driven by the effectiveness of HF in dissolving minerals in sandstone and HCl in controlling precipitation. Nonetheless, high temperature matrix acidizing approach is in growing need since many wells nowadays are producing from much deeper and hotter reservoir, with a temperature higher than 200°F. In such conditions, mud acid causes rapid reaction rates, hence becoming less efficient as the acids are consumed too early. Furthermore, mud acid is hazardous and very corrosive. On the contrary, previous studies had shown that Fluoroboric Acid (HBF4) and Phosphoric acid (H3PO4) offered numerous advantages in comparison to the conventional mud acid. HBF4can hydrolyze to form HF whereas H3PO4acts as a buffer acid; which is able to penetrate deeper into the formation before spending. Likewise, both acids cause more increase in the permeability, less change in the strength of core samples and significantly less corrosive. This paper had critically reviewed the experimental works which had been done on different types of acids. The advantages and disadvantages of these acids are evaluated. Therefore, a new acid combination (HBF4:H3PO4) is developed and the future work which can be done on it is proposed.